Factors Influencing Language Development in Preschool Children in Karanganyar Regency, Central Java - Mangunsong, Roy Romey Daulas; Sutanto, Alfiani Vivi; Sudarman, Sudarman (PT Inovasi Pratama Internasional, 2024)
Children under five years old are an important period in a child's developing body. Child growth and development is a continuous process, not only experiencing physical growth, brain development, there is also a learning process in the development of intelligence, motor skills, speech, language and social and independence. Fulfillment of nutrition is very necessary to support good child growth and development.The purpose of this study was to analyze the factors that influence the language development of preschool children in Karanganyar Regency, Central Java. Subjects and Methods: This study used a cross-sectional research design, which was conducted in Karanganyar Regency, Central Java from April to August 2024. A sample of 112 children was selected using a purposive sampling technique. The dependent variable is language development. The independent variables are cognitive ability, stunting, breastfeeding, immunization and gender. Data collection using questionnaires and analyzed by logistic regression using Stata 13. Results: The language development of preschool children can be delayed in children with cognitive abilities (b = 2.52; 95% CI = 0.03 to = 0.28; p = 0.013), stunting (b = 2.82; 95% CI = 0.05 to 0.30; p = 0.006), non-exclusive breastfeeding (b = 2.97; 95% CI = 0.07 to 0.38; p = 0.004), in boys (b = 7.2; 95% CI = 0.33 to 0.28; p <0.001), and children with incomplete immunization. Conclusion: The language development of preschool children is related to children's cognitive abilities, the incidence of stunting, non-exclusive breastfeeding, incomplete immunization and male gender.